Single-cell RNA sequencing in human atherosclerotic plaques reveals a novel smooth muscle cell subtype that possesses multi differentiation potential and shapes the microenvironment - Ye, Weijie; Chen, Zhibing; Xia, Zhiwei; Li, Dongjie (Clinical and experimental medicine, 2025)
Smooth muscle cells (SMCs) play a crucial role in atherosclerosis, undergoing proliferation, migration, and transdifferentiation into other cell types. Multiple SMC subsets exist, each with distinct roles that are increasingly being elucidated. To investigate the heterogeneity of SMC subsets in lesion, we integrated three single-cell RNA sequencing datasets. Bioinformatics analysis was conducted to evaluate the effects of the immune microenvironment, biological function, metabolic interactions, and differentiation potential of different SMC subsets. Atherosclerotic plaques from ApoE −/− mice were used for validation. We employed pySCENIC to predict the transcription factors associated with different SMC subsets and used bulk RNA sequencing data to identify the function of the_C5 marker gene (ALDOA). We identified a unique smooth muscle cell cluster 5 (SMC_C5) in human coronary plaques and confirmed its presence in aortic plaques of ApoE −/− mice. SMC_C5 interacts with macrophages and monocytes, influencing the microenvironment and participating in various pathways and metabolic processes. Additionally, SMC_C5 cells exhibit pluripotent differentiation potential. Mechanistically, we found a strong association of SMC_C5 and the transcription factor GA binding protein 1 (GABP1). The SMC_C5 marker gene (ALDOA) was involved in regulating metabolism, hypoxia response, and the immune microenvironment. This investigation provides novel insights into the complex biology of SMCs and reveals novel functions of SMC_C5 in atherogenesis.